A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMAN 1 GAUNG INDRAGIRI HILIR IN COMPREHENDING REPORT TEXTS - Aulia Tresna Ningtyas; FakhriRas FakhriRas; Erni Erni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This descriptive research was aimed at finding out how the ability of the second year students of SMAN 1 Gaung in comprehending Report texts. The sample was XI IPA 1 (30 students) chosen by cluster random sampling technique. The result showed that the reading ability of the second year students of SMAN 1 Gaung in comprehending report text is in good level with the mean score was 62.42. However, this score was lower than the minimum score criteria is 70.00. The most difficult aspect in comprehending report text was in finding factual information is 53.2 which was categorized into mediocre level. Then, the easiest aspect was in finding reference 75.3 which was categorized into good level. Based on research finding, it would be better to recommend as the follow. First, the students need to have more practice in finding factual information ability in reading activity. Second, the English teacher may increase the students’ motivation and encourage them to read report text in English book as a part of practicing activities of comprehending report texts.Keywords: Study, Ability, Report Text.